An evaluation of supplemental Vitamin D3 on growth performance of pigs pre- and postweaning, nursery feed preference, and serum 25(OH)D3 - J R Flohr; Steven C Henry; M L Potter; N S Shelton; L Greiner; J Conner; C W Hastad; D Murray; R Cain; K Frerichs; E L Hansen; E Fruge; et al. (Kansas Agricultural Experiment Station Research Reports, 2012)
Three experiments were conducted to evaluate the effects of supplementing different concentrations and sources of vitamin D3 on pig performance, feed preference, and serum 25(OH)D3. In Exp. 1, a total of 398 barrows from 80 litters (PIC 1050, initially 7 d of age) were used in a 38-d study in a 2 × 2 factorial to determine the effects of vitamin D3 suppleÂ¬mentation from either a single oral dose or from high levels of vitamin D3 in early nursÂ¬ery diets on pig performance and serum 25(OH)D3. On d 7 after birth, matched sets of pigs within litters were allotted to 1 of 2 oral dosages (none or 40,000 IU vitamin D3) in a randomized complete block design. Pigs were weighed at d 7 and at weaning (d 21). Following weaning, a subset of 300 barrows were used from d 21 to 45 to determine the effects of the previously administered oral vitamin D3 and 2 levels of dietary vitamin D3 (625 or 6,250 IU/lb; 0.80% Ca and 0.63% available P) from weaning to d 31 on pig growth and serum 25(OH)D3. A common diet containing 625 IU/lb of vitamin D3 (0.70% Ca and 0.47% available P) was fed from 31 to 45 d of age. No dose × diet interÂ¬actions (P>0.09) were observed. Serum 25(OH)D3 increased (P<0.01) on d 21 and tended to increase on d 31 after dosing pigs with oral vitamin D3 prior to weaning. On d 31, serum concentrations increased with increasing dietary vitamin D3 levels (P<0.01). Weaning weight was not influenced (P>0.17) by the oral dose of vitamin D3. Supplementing vitamin D3 by either dose or diet did not influence (P>0.23) nursÂ¬ery performance. In Exp. 2, a total of 864 pigs (PIC TR4 × FAST ADN, initially 21 d of age) were used in a 30-d study to determine the effects of water supplementation of vitamin D3 on nursery growth performance and serum 25(OH)D3. Upon arrival to the nursery (d 0), pigs were allocated to pens and pens were randomly allotted to 1 of 2 water vitamin D3 supplementation treatments (none or 4,000,000 IU/gal). There were 24 pigs/pen and 18 pens/treatment. Pigs were provided the water supplementation treatments from d 0 to 10. From d 10 to 30, pigs were administered water with no supplemental vitamin D3. Common diets were fed throughout the study and were formulated to contain 1,000 IU/lb added vitamin D3. Twelve pigs per treatment were randomly selected to be bled on d 0, 10, 20, and 30 to determine serum 25(OH)D3 concentrations. Water supple-mentation of vitamin D3 increased (P<0.01) serum 25(OH)D3 concentrations on d 10, 20, and 30 of the study but did not affect (P>0.15) nursery growth performance. In Exp. 3, 72 pigs (PIC 327 × 1050, initially 28 d of age) were used in 2 14-d feed preference comparisons to determine whether pigs discriminate in their choice of feeds containing different concentrations of vitamin D3. On d 0, pigs were weighed and allotted to pens based on BW with 6 pigs/pen and 6 pens per feed comparison. The first preference comparison was between diets containing either 625 (control) or 6,250 IU/ lb vitamin D3, and the second comparison was between diets containing 625 (control) or 20,000 IU/lb vitamin D3. Total pen feed intake was measured, and intake of each diet was expressed as a percentage of total intake. The percentage of feed intake did not differ (P>0.14) between the control diet and the diet containing 6,250 IU/lb, but pigs chose to consume a greater percentage (P<0.01) of the control diet (77%) than the diet containing 20,000 IU/lb of vitamin D3. These experiments demonstrated that providing high levels of vitamin D3 in an oral dosage, in the water, or in feed increased serum 25(OH)D3; however, preweaning and nursery pig growth performance was not influenced by elevating vitamin D3 above normal dietary levels.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; Nursery pig; Vitamin D